Peningkatan Hasil Belajar Materi Pecahan Melalui Penerapan Media Kartu Pecahan. Pada Siswa Kelas IV MIS Nurul Misbah Bombaru Desa Tribur Kecamatan Abad Selatan Tahun Pelajaran 2024/2025 - Lehidonu, Andriyani Tahir; Amsidi, Istiqamah; Pakro, Pahlawan (Jurnal Edukasi, 2026)
Improving Learning Outcomes in Fractions Through the Application of Fraction Card Media in Grade IV Students of MIS Nurul Misbah Bombaru, Tribur Village, South Abad District for the 2024/2025 Academic Year. Andriyani T. Lehidonu, 211530281035 This research, conducted by Andriyani T. Lehidonu, utilized a Classroom Action Research method to improve student learning outcomes in fractions. The subjects were 9 students from Grade IV MIS Nurul Misbah Bombaru, with an individual Minimum Mastery Criterion (KKM) of 75 for mathematics.Data was collected using observation sheets for teacher and student activities, as well as test results. The data analysis technique used a percentage formula. The research findings show that: In Cycle I: Teacher activity reached 66.6%, and student activity was also 66.6%. In Cycle II: Teacher activity increased to 83%, and student activity significantly improved to 95%.This study demonstrates that the application of fraction card media led to an increase in teacher activity, student activity, and learning outcomes. Initially, in Cycle I, although the media was used, the teacher's teaching method still needed improvement in classroom management and motivation. This resulted in low student participation and a failure to achieve learning mastery. The classic mastery percentage was only 33.3%, with an average score of 66.4, and only 3 out of 12 students reaching the KKM. This figure was well below both the individual KKM (75) and the classical KKM (80%).However, after the teacher made improvements in Cycle II, such as more actively controlling group discussions, asking sequential questions, and providing appreciation, the media successfully stimulated students' thought processes. This made them more active and independent in learning and significantly improved their understanding of simple fraction comparisons. As a result, the students' average score sharply increased to 88.9, and the student learning mastery percentage reached 79.4%. The number of students who achieved the KKM increased to 8. Kata Kunci: Fraction Learning Outcomes, Fraction Card Media, Elementary Students